Diagnostic Evaluation of HPV DNA Test in Detecting Cervical Pre-Cancer: A Systematic Review - Ferdous, Jannatul; ., Ashrafunnesa; Munshi, Saifullah; Khan, Md Maruf Haque; Parvin, Mohuwa; ., Hridi; Bushra, Tanjela; Haseen, Fariha (Journal of Posthumanism, 2025)
Cervical cancer remains a significant global health challenge, particularly in low- and middle-income countries, due to limited access to effective screening programs. Persistent infection with high-risk human papillomavirus (HR-HPV) is recognized as the primary etiological factor for cervical cancer. Although cytology-based screening methods such as the Pap smear and liquid-based cytology (LBC) have historically served as the cornerstone of early detection, their sensitivity limitations have prompted the investigation of HPV DNA testing as an alternative or adjunctive screening strategy. This systematic review aimed to evaluate and compare the diagnostic accuracy of HPV DNA test, which detects HPV 16, HPV 18, and 12 other high-risk HPV genotypes, with conventional cytology methods (Pap test and LBC) and visual inspection with acetic acid (VIA) in detecting high-grade cervical intraepithelial neoplasia (CIN2+) as part of primary cervical cancer screening. The review was conducted in accordance with PRISMA guidelines. A comprehensive literature search was performed using PubMed, Google Scholar, and Medline to identify relevant studies published in English. Six studies were ultimately included, comprising one randomized controlled trial and five cross-sectional studies. The findings consistently demonstrated that HPV DNA testing, exhibits significantly higher sensitivity than cytology or VIA for detecting CIN2+ lesions, though with slightly reduced specificity. Combining cytology or VIA with HPV DNA testing further improved sensitivity but resulted in lower specificity. While these results highlight the superior detection capability of HPV-based testing, the long-term impact on reducing cervical cancer incidence and mortality requires further validation through ongoing and future randomized trials.